Digital Content Analysis of Community Identity Presented Through YouTube Platform by YouTubers: A Case Study of Ban San Charoen, Tha Wang Pha District, Nan Province: การวิเคราะห์เนื้อหาดิจิทัลของอัตลักษณ์ชุมชนที่เสนอผ่านแพลตฟอร์มยูทูบโดยยูทูบเบอร์: กรณีศึกษาบ้านสันเจริญ อำเภอท่าวังผา จังหวัดน่าน - Trakansiriwanich, Keerati; Untong, Akarapong; Kiratikarnkul , Siriporn (Mekong-Salween Civilization Studies Journal, 2025)
This research aims to analyze the presentation perspectives of Ban San Charoen tourism community’s identity, as well as to analyze and synthesize the perception creation, discourse presentation, and impacts of such presentations by YouTubers on the YouTube platform. The study applies qualitative phenomenological research methodology through non-participatory observation of 130 video clips, coupled with thematic analysis and content analysis of 35 video clips presented during 2017-2025. The findings reveal that YouTubers present the community identity in four main forms: 1) the creation of a "hidden paradise" image, 2) historical storytelling and transformation from opium cultivation areas to quality coffee production sites, 3) presentation of challenges and adventure, and 4) depiction of the unique lifestyle and culture of the Mien people. The perception of community identity by YouTubers is constructed through four key discourses: natural beauty, high-quality coffee, model community status, and adventure tourism. These presentations have caused the community to adapt in response to the portrayed image. The research suggests that the community should develop internal communication processes that align with the externally perceived image and create digital information to establish appropriate understanding and expectations for visitors.